2022
DOI: 10.1007/s00784-021-04297-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of P11-4 for the treatment of periodontal defects in dogs

Abstract: Objectives This study’s aim was to investigate the safety and performance of a self-assembling peptide matrix (SAPM) P11-4 for the treatment of periodontal disease in a controlled pre-clinical study. Materials and methods Acute buccal bony dehiscence defects (LxW: 5 × 3 mm) were surgically created on the distal root of four teeth on one mandible side of 7 beagle dogs followed by another identical surgery 8 weeks later on the contralateral side. SAPM P11-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Two systematic reviews that investigated enamel matrix derivatives in periodontal therapy concluded that enamel matrix could both significantly improve clinical attachment levels and result in reduced pocket probing depth compared to open flap debridement alone [120,121]. The EMD appears to positively influence PDL cells, cementoblasts, and osteoblasts while inhibiting epithelial cells-a characteristic favorable for the re-establishment of the periodontal tissues [122]. Another review on this topic, which only analyzed studies conducted on human samples, suggests that, although several studies have been conducted to evaluate the efficacy of the EMD in terms of periodontal wound healing and complications, further investigation is needed [123].…”
Section: Enamel Matrix Derivativesmentioning
confidence: 99%
“…Two systematic reviews that investigated enamel matrix derivatives in periodontal therapy concluded that enamel matrix could both significantly improve clinical attachment levels and result in reduced pocket probing depth compared to open flap debridement alone [120,121]. The EMD appears to positively influence PDL cells, cementoblasts, and osteoblasts while inhibiting epithelial cells-a characteristic favorable for the re-establishment of the periodontal tissues [122]. Another review on this topic, which only analyzed studies conducted on human samples, suggests that, although several studies have been conducted to evaluate the efficacy of the EMD in terms of periodontal wound healing and complications, further investigation is needed [123].…”
Section: Enamel Matrix Derivativesmentioning
confidence: 99%
“…In Veterinary Medicine, to our knowledge, there are no studies on MD of dental tissues in canine and feline species. However, a study was recently published that integrated the measurement of MD of the alveolar bone in dogs using mCT [ 11 ]. The determination of feline teeth MD using the proposed technique could be helpful in the characterization of dental pathology in cats, such as developmental abnormalities such as enamel hypoplasia or acquired ones such as odontoclastic tooth resorption, or neoplastic lesions with dental involvement.…”
Section: Introductionmentioning
confidence: 99%